The PASTA Bridge: A Technique for the Arthroscopic Repair of PASTA Lesions - Hirahara, Alan M. (Arthrosc Tech, 2017)
PASTA (partial articular supraspinatus tendon avulsion) lesions of greater than 50% thickness are usually repaired, whereas those of less than 50% thickness receive subacromial decompression and debridement. However, tears of greater than 25% thickness of the tendon result in increased strain of the adjacent, intact tendon fibers. Re-creating the tendon footprint at the greater tuberosity is the goal of a repair. Transtendon repairs have been considered the gold standard in repair but have shown varying outcomes and are technically difficult procedures. This report details the PASTA bridge—a technique for the arthroscopic, percutaneous repair of PASTA lesions. The PASTA bridge uses a spinal needle to ensure the repair includes the leading edge of the good tissue and is at the appropriate angle and area. Most procedures use a knife or trocar blindly to access the joint to place anchors, which has the potential to damage surrounding tissues and result in poor anchor and suture placement. The PASTA bridge is a safe, reliable procedure that is easily reproducible and appropriate for surgeons of all experience levels and should be strongly considered when repairing PASTA lesions.